2022
DOI: 10.7759/cureus.23235
|View full text |Cite
|
Sign up to set email alerts
|

A Patient’s Six-Month Journey From Low Sodium to Blue Toes to Stroke: Non-infective Thrombotic Endocarditis Due to Non-small Cell Lung Cancer

Abstract: We report a patient's journey with a four-year history of hypertension (HTN) and hyperlipidemia (HLD), stable on beta-blocker and statin, monitored every six months by alternating visits between her cardiologist and primary care physician (PCP) in North Carolina (NC). Six months before relocating to New York (NY) she had been informed about incidental severe hyponatremia during her last outpatient visit, the need for repletion with sodium chloride tablets, and the critical importance of prompt follow-up to rul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Another report described CT findings of a single cavitary lesion, later pathologically confirmed as adenocarcinoma [ 11 ]. Two additional cases reported echocardiogram findings suggestive of infective endocarditis; one such case diagnosed NBTE of the mitral valve in a patient with known stage 4 malignancy [ 12 ]. Another case presented initially with acute deep venous thrombosis and pulmonary embolism with an incidentally identified lung mass; subsequently, this patient developed additional thrombotic events eventually leading to the diagnosis of NBTE of the mitral valve in the setting of large cell carcinoma [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another report described CT findings of a single cavitary lesion, later pathologically confirmed as adenocarcinoma [ 11 ]. Two additional cases reported echocardiogram findings suggestive of infective endocarditis; one such case diagnosed NBTE of the mitral valve in a patient with known stage 4 malignancy [ 12 ]. Another case presented initially with acute deep venous thrombosis and pulmonary embolism with an incidentally identified lung mass; subsequently, this patient developed additional thrombotic events eventually leading to the diagnosis of NBTE of the mitral valve in the setting of large cell carcinoma [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…It further demonstrated that factors such as splenic infarction, renal infarction, pulmonary embolism, and mitral valve regurgitation (all present in the patient in our case) were among the factors associated with an increased risk of in-hospital mortality. [25] There are case reports of favorable evolution in patients with advanced lung cancer with driver mutation [26] and without this description, [27] however, NBTE generally had a poor prognosis in most identified cases, particularly in those with lung cancer or metastatic tumours. [28] The present case is peculiar due to its favorable evolution.…”
Section: Demonstrationmentioning
confidence: 99%